## (Would be very much appreciated if it was answered asap, please and thank you! =D) The equation 3.3x − 6.6 = 2.7x can be transformed t

Question

(Would be very much appreciated if it was answered asap, please and thank you! =D)

The equation 3.3x − 6.6 = 2.7x can be transformed to form which of the following expressions?

6.0x = 6.6

0.6x = 6.6

6.0x = −6.6

0.6x = −6.6

in progress
0

Math
2 weeks
2021-10-13T06:03:21+00:00
2021-10-13T06:03:21+00:00 1 Answer
0
## Answers ( )

The equation 3.3x – 6.6 = 2.7x is equal to the expression 0.6x = 6.6 (2nd option)